(untitled) (Fiep Bulletin - online, 2015)
The objective of the present study was to evaluate the palmar prehension force between dominant and non-dominant hand of bodybuilders. Participated in the study 20 individuals, aged between 20 to 35 years bodybuilders, training regularly 3 times a week. For analysis of the palmar prehension force was used the dynamometer Takei ® Manual Mechanical measuring the strength depending on the amount of tension produced, with a capacity of 0 to 100 KP (kilogram force) previously calibrated. For comparison analysis between grip force of dominant and non-dominant hand pre and post-test was used the t Student "test with a significance level of p 0.05. You can identify the males average FPP of dominant hand (MD) in pre-test was 57.30 Kg at post-test was 56.85 Kg and a decrease in strength. The same occurred in non dominant hand (MND) where the pre-test average was 55.95 Kg and post-test 53.80 Kg, however when we performed the statistical analysis was not statistically significant. In the female the average MD FPP in the pre-test was 29.75 Kg, at post-test was 29.45 Kg there is a decrease in strength. However the average FPP of MND in the pre-test was 29.10 Kg, already in the post-test was of 29.70 Kg was observed an increase in strength, but not demonstrated no statistically significant difference between pre and post-tests. It is concluded that, in the present study the FPP of individuals male bodybuilders and female, compared MD and MND there was no significant difference between the sides.